Grain-size Characteristics and Net Transport Patterns of Surficial Sediments in the Day River Estuary - Thanh, Dinh Xuan; Quan, Nguyen Hong; Thi Huyen Trang, Nguyen; Nhan, Tran Thi Thanh; Huu, Vu Cong (VNU Journal of Science: Earth and Environmental Sciences; Vol 40 No 2, 2024)
The Day estuary area is accreting relatively quickly, expanding the land area for Nam Dinh and Ninh Binh provinces. To understand the sediment accreting mechanism in this region, 42 surficial sediment samples were taken and analyzed for grain size to determine the rules of surficial sediment distribution and analyze the net sediment transport pattern. Research result shows that in the Day estuary area: sand is mainly dominated in the east and south, silty sand is distributed in front of the estuary and south of Con Noi, and sandy silt is distributed in the west and center of the study area. The coarsest-grained sediments are distributed in the North and South, while finer-grained sediments occupy the main area in the East and finest-grained sediments are spread out in the West of the study area. Well-sorted sediments are dominated throughout the region, covering the center and the East of the study area, showing that the hydrodynamic regime is relatively stable. Medium-sorted sediments are distributed in the West, North, and South, reflecting a less stable hydrodynamic regime. Poorly-sorted sediments at the Day estuary mouth represent the most complex hydrodynamic conditions here. Sediment tends to be transported from the southeast and west to the central area, causing a strong accretion process to create Con Noi and shallow mild tidal flats in the Day estuary area.